Teacher Communication Strategy in the Practice of Moral Values at SMK Telkom Medan - Riduan Riduan; Candra Wijaya; Hasnun Jauhari Ritonga (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2022)
This study aims to analyze the teacher's communication strategy in the practice of moral values at SMK Telkom Medan and to analyze the supporting and inhibiting factors of the teacher's communication strategy as well as the stages of implementation in the practice of morals at SMK Telkom Medan. The methodology used in this research are; a qualitative approach of the type of field research (field research) which is descriptive. With primary and secondary data sources. As well as data collection techniques through interviews (interviews) with informants 10 teachers and several students, observation and documentation. The collected data is then analyzed by means of reduction, presentation and verification of data so that a conclusion can be drawn. The results showed that the communication strategies used by the teachers at SMK Telkom Medan were; by using interpersonal communication strategies in both verbal and nonverbal forms, strategies to identify communication targets, compiling messages, method determination strategies by means of Repitition/redundancy, Informative, Persuasive, educative, Caursive, selection of communication media used.